2018
DOI: 10.1108/jima-02-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muslims’ acceptance of imported products with halal logo

Abstract: Purpose This study aims to examine whether citizens of non-Muslim countries accept products with a “halal” logo. In the era of globalization, one of the most crucial issues for Muslim travelers is reliable halal foods when visiting non-Muslim countries. If people in non-Muslim countries accept imported products containing halal certification logos, and such products are readily available in shops, this issue could be substantially improved. Design/methodology/approach Malaysia and Japan were selected as Musl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
(27 reference statements)
1
24
0
1
Order By: Relevance
“…This result was consistent with existing studies. For example, Kawata, Htay, and Syed (2018) examine the non-Muslim acceptance of halal foods (mineral water) and their results demonstrated that non-Muslims show positive additional WTP for the halal logo. One of the possible reasons that citizens, in general, show additional WTP for the halal logo was that non-Muslims regard the halal logo as equivalents of other similar certificates such as HACCP.…”
Section: Examination Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was consistent with existing studies. For example, Kawata, Htay, and Syed (2018) examine the non-Muslim acceptance of halal foods (mineral water) and their results demonstrated that non-Muslims show positive additional WTP for the halal logo. One of the possible reasons that citizens, in general, show additional WTP for the halal logo was that non-Muslims regard the halal logo as equivalents of other similar certificates such as HACCP.…”
Section: Examination Of Hypothesesmentioning
confidence: 99%
“…The same and/or similar halal products have a different value if non-Muslims are involved. Not a few studies examine if or not non-Muslim consumers accept halal products (Mathew, Abdullah, and Ismail, 2014;Wibowo and Ahmad, 2016;Kawata, Htay, and Syed, 2018); some existing studies check if Muslims accept halal packaged products prepared by non-Muslims (Yunus et al, 2014;Manan, Ariffin, Maknu, Ibrahim, and Jaafar, 2019); others consider halal tourisms in non-Islamic countries (Battour and Ismail, 2016;Putit, Muda, Mahmood, Ahmad Taufek, and Wahib, 2016;Han, Al-Ansi, Olya, and Kim, 2019). These existing studies imply that the same halal products may have different values because of the involvement of non-Muslims in the process.…”
Section: Introductionmentioning
confidence: 99%
“…This includes various aspects related to food intake and the normative attire of followers of Islam; various other norms and daily lifestyles are included (Al-Gahhar 2016; Khan & Callanan, 2017;Kawata et al, 2018).…”
Section: Sharia Law Is Associated With Various Regulations and Limitamentioning
confidence: 99%
“…The halal catering industry is not only an important bearer of halal food culture but also an indispensable economic and cultural unit of the Halal Food Culture Circle, which has the function of embodying and inheriting the characteristics of halal food culture (Battour, M., 2017). Through training, the halal catering industry has ensured that service personnel have a certain understanding of brand allusions, creative ideas, production techniques, raw materials, and the nutritional value of various halal foods (Battour, 2017 (Khan & Callanan, 2017;Kawata et al, 2018). The cooking shapes that will attract attention and the whole process really makes you feel a unique pleasure of halal food culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The emerging of Halal tourism has motivated Indonesia to be one of the biggest player in the industry. Halal tourism is not only popular among Islamic countries or countries with majority of Muslim population, but also in some non-Muslim countries, such as Japan, South Korea and Thailand (See, Kawata et al, 2018;Yousaf and Xiucheng, 2018;Han, et al, 2019;Wannasupchue et al, 2019). It is believed that the industry of Halal tourism has potential economic multiplier effects for the respected country.…”
Section: Halal Tourismmentioning
confidence: 99%